The Crisis of Spirituality in the Late Middle Ages: From the Twelfth Century to the Protestant Reformation; with an Emphasis on the Reformatio Sigismundi (1439) (Global Journal of Human-Social Science, 2019)
The Protestant Reformation was not as previous scholars have already pointed out numerous times a sudden and unexpected development Instead it represented the outcome of a long-term paradigm shift This paper examines the larger literary framework and then focuses on one of the crucial texts from the late Middle Ages where most of the ideas as formulated by Luther in 1517 and later were already expressed in more or less the same way The loss of spirituality is commonly identified as one of the central concerns both already in the high Middle Ages and here in the Reformatio Sigismundi